Comparing silicon mineral species of different crystallinity using Fourier transform infrared spectroscopy - Ellerbrock, Ruth H.; Stein, Mathias; Schaller, Jörg (Frontiers in Environmental Chemistry, 2024)
In soils, various solid silica (Si) species exhibit different weathering behaviors and surface reactivities, which are among others related to the crystallinity of the silicate tetrahedral network. Amorphous species exhibit faster weathering and generally possess a larger specific surface area in comparison to crystalline species. However, the characterization of these different species is commonly based on wet chemical extraction methods which lack selectivity. While Fourier-transform infrared spectroscopy (FTIR) in the mid-infrared range can differentiate between short-range ordered aluminosilicates (SROAS) and pure amorphous silica (ASi), systematic studies on the IR spectral features that distinguish solid Si species by crystallinity are limited. This study aims to identify FTIR absorption bands that can differentiate Si species based on their crystallinity. Our data clearly shows that ASi can be distinguished from very crystalline silica (quartz), and sea sand. The absorption band at about 800 cm -1 in the FTIR spectra allows to determine the degree of crystallinity of the studied ASi species since the band becomes smaller and the band maximum shifted towards lower wavenumbers with increasing degree of crystallinity. Hence, FTIR spectra may be used to differentiate certain Si species in complex samples like soils, allowing to estimate weatherability and surface reactivity of those species.